REVIEW: AN EFFORTS TO INCREASE THE SOLUBILITY AND DISSOLUTION OF ACTIVE PHARMACEUTICAL INGREDIENTS - SOPYAN, IYAN; GOZALI, DOLIH; MEGANTARA, SANDRA; WAHYUNINGRUM, RETNO; SUNAN KS, INSAN (International Journal of Applied Pharmaceutics, 2022)
The most significant aspect of a drug's physicochemical nature is its solubility. If the medicine is in a dissolved form, it can dissolve and enter the membrane, resulting in a therapeutic effect. The pharmacokinetic phase of the drug in the body, which includes absorption, distribution, metabolism, and excretion, will be correlated with solubility. Some medications, however, have a low solubility. To obtain a therapeutic impact, an effort must be made to increase the drug's solubility. Based on the literature research, the goal of this paper is to explain approaches that can be utilized to improve solubility. In general, physical, chemical, and micelle formation efforts can all be used it to enhance solubility. Particle size reduction, crystal shape modification, and the utilization of matrices in the disperse phase are examples of physical alterations. pH adjustment, buffering, salt formation, complexation, and derivatization all are examples of chemical alterations. The employment of supercritical processes in solutions and also excipients such as surfactants, cosolvents, stabilizing solutions, and others are examples of how micelle formation can be modified.